Hypofractionated whole breast radiotherapy: current perspectives - Koulis TA (Dove Medical Press, 2015)
Theodora A Koulis, Tien Phan, Ivo A Olivotto Department of Oncology, University of Calgary, Tom Baker Cancer Centre, Calgary, AB, Canada Abstract: Adjuvant radiotherapy (RT) is an important part of breast cancer management but the dose and fractionation schedules used are variable. A total of 50 Gy in 25 daily fractions delivered over 5 weeks is often considered the "standard" adjuvant RT prescription. Hypofractionated regimes such as 42.5 Gy in 16 daily fractions or 40 Gy in 15 daily fractions following breast-conserving surgery have proven to be equally effective and achieve similar or better cosmetic and normal tissue outcomes for both invasive and in situ diseases and when treating the regional nodes. Hypofractionation is more convenient for patients and less costly. However, certain patients at higher risk of RT late effects may benefit from a less intense, even more extended fractionation schedule. This review describes the indications for whole breast hypofractionated adjuvant RT for patients with breast cancer following breast-conserving surgery and proposes that hypofractionation should be the new "standard" for adjuvant breast cancer RT. Keywords: fractionation, breast cancer, cosmesis, radiotherapy